Separateness of underground garage premises (selected issues) - Kucharski, Krzysztof (Studia Iuridica Toruniensia, 2024)
The subject of the analysis in this article is the problem of fulfillment by an underground car park of the prerequisites of separateness of premises within the meaning of the Act on ownership of premises. The first part of the article relates to the possibility of recognizing an underground car park as a building within the meaning of the Construction Law. The second part refers to the possibility of considering a garage facility as a separate non-residential unit. In particular, a situation was taken into account in which the investor requests a certificate of separateness for more than one set of premises in the building while the possibility of pedestrian crossing and vehicle passage is foreseen between the premises.